PENGARUH STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN HUTANG SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN SEKTOR ANEKA INDUSTRI YANG TERDAFTAR DI BEI TAHUN 2018-2020 - Apriliyanti, Yunita Indri; Wahyuni, Ika; Pramitasari, Triska Dewi (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
Multi-Industrial Sector Company is one type of business that is growing rapidly in Indonesia. A multi-industrial sector company is one of the companies listed on the Indonesia Stock Exchange and is considered more productive and can provide wide-ranging effects so as to increase the added value of raw materials, increase workforce, produce various consumer needs, generate foreign exchange sources, and contribute to taxes and largest customs. The purpose of this study was to determine the effect of Ownership Structure on Firm Value with Debt Policy as an intervening variable in Multi-Industrial Sector companies listed on the Indonesia Stock Exchange in 2018-2020. The population of this study is all companies in the various industrial sectors listed on the Indonesia Stock Exchange for the 2018-2020 period as many as 51 companies. The sampling technique was determined by purposive sampling. Data analysis and hypothesis testing in this study used the Structural Equation-Partial Least Square (PLS-SEM) method. The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that ownership structure has a negative but not significant effect on debt policy, ownership structure has a negative but not significant effect on firm value, debt policy has a significant positive effect on firm value. The results of the indirect effect hypothesis test show that the ownership structure has a positive but not significant effect on firm value through debt policy.